Developing Google Sites-Based Interactive Learning Media for Teaching News Texts to Seventh-Grade Students - Nenk Tazkiatus Soliha; Eri Sarimanah; Stella Talitha; Roy Efendi (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to describe teachers' and students' needs for learning media, develop an integrated Google Sites-based interactive learning media for seventh-grade news text instruction using the ADDIE model, and evaluate its validity, practicality, and effectiveness. Methodology: Employing a research and development (R&D) approach using the ADDIE model, this study evaluated the media's effectiveness through a one-group pre-test and post-test design. The participants included 36 seventh-grade students at SMPN 2 Babakan Madang, one Indonesian Language teacher, and three expert validators. Data collection involved interviews, questionnaires, validation sheets, and learning outcome tests, analyzed through qualitative descriptions and quantitative statistical measurements. Main Findings: The developed Google Sites-based interactive learning media was found to be very valid, with content validity at 99%, media validity at 98%, and final language validity at 90%. It is also highly practical, receiving a 100% positive response from the teacher and 95% from students. Student learning outcomes improved, showing a mean score increase of 37.88 points. The N-gain score was 0.63 (moderate category), and a paired sample t-test showed a significant difference (p = 0.001 < 0.05). Novelty/Originality of this study: The novelty of this study lies in the development of an integrated Google Sites-based learning medium that combines news text materials, contextual examples, interactive exercises, and structured navigation to support seventh-grade students’ learning within the ADDIE framework.